Management of secondary immunodeficiency in hematological malignancies: a Delphi consensus from the Middle East - Dimou, Maria; Abuzakouk, Mohamed; Al Ahmad, Mona; Al Farsi, Khalil; Alhuraiji, Ahmad; Al Roqi, Fayhan; Alsaeed, Ahmed; Alzahrani, Mohsen; Bazarbachi, Ali; Cherif, Honar; El Fakih, Riad; Irani, Carla; et al. (Frontiers in Hematology, 2024)
Secondary immunodeficiency (SID), acquired hypogammaglobinemia, is an immunodeficiency caused by different factors like diseases, medications, and/or nutrition disorders. Most patients with hematological malignancies (HM), namely chronic lymphocytic leukemia (CLL) and multiple myeloma (MM), experience such SID. These patients have a consistently high risk of infection throughout the disease course. Traditional chemotherapy and novel agents used to treat HM may further increase infection susceptibility. Immunoglobulin replacement therapy (IgRT) is an effective management option for SID. The prevalence of SID in the Middle East needs better documentation. Healthcare providers should consider and evaluate SID in patients at risk, monitor for infection occurrence, and treat accordingly (including initiating IgRT when indicated). A Delphi initiative was conducted by a consensus panel of 15 experts from the Middle East who have over 20 years of experience in actively managing patients with SID. The modified Delphi process was used, and 16 questions reached a consensus on managing SID patients with IgRT. In addition, the consensus panel of Middle East experts recommended real-world practice recommendations regarding initiating, dosing, and discontinuing IgRT in managing SID. This consensus recommendation aims to assist healthcare practitioners in the Middle East in evidence-based clinical decision-making for better management of SID.